Investigation of perceived stigma among people living with human immunodeficiency virus/acquired immune deficiency syndrome in Henan Province, China - Zhen Li; Yu Sheng (Elsevier, 2014)
Purpose: To investigate the level of and factors influencing perceived stigma and discrimination among people living with human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (PLWHA) in Henan Province. Methods: In total, 161 PLWHA from Zhengzhou and Zhenping were investigated using the Berger HIV stigma scale. Results: The mean Berger stigma scale score was 105.70 ± 15.20, indicating a middle stigma level. Among the four subscales of the Berger stigma scale, the disclosure concerns score was highest, while the negative self-image score was lowest. Multivariate analyses showed that factors influencing perceived HIV stigma included the level of education and route of infection. Conclusion: The level of perceived HIV stigma and discrimination among PLWHA in Henan Province is moderate and was affected by the level of education and route of infection. Special intervention should be established to address this problem.